The Relationship of Macronutrient Intake with Physical Fitness in Sokowaten Baru Primary School Students - Ihsan Fahroji; Sunarti Sunarti; Dyah Suryani (Poltekkes Kemenkes Mataram, 2024)
Background: Physical fitness can be defined as the body's body's ability or capacity to perform all forms of physical activity in daily life without excessive fatigue. Everyone must be physically healthy to carry out activities effectively and efficiently. Based on the results of observations that were made in October 2023 on 15 students from randomly selected research locations, it is found that 13 out of 15 students need physical fitness of less than 60 VO2MAX. This is because these eight students rarely do physical activity and more often play games in their spare time; besides that, there are 9 out of 15 students who do not have breakfast before going to school. This is another factor causing students to lack physical fitness. Sokowaten Baru Primary School has adequate learning facilities. Still, there needs to be improvements for physical fitness education, such as sports equipment that has been damaged and cannot be used compared to other schools in Yogyakarta City.Research Purposes: This study aimed to determine the relationship between macronutrient intake and physical fitness in students at Sokowaten Baru Primary School, Bantul Regency.Research Methods: The research design used was cross-sectional. The population was 432 students, and the sample size was 59 respondents. The study was conducted by proportional random sampling with sampling criteria aged 10-11 years. Data were collected by completing a 24-hour food recall questionnaire and the Harvard test.Research Result: The results showed a relationship between carbohydrate (p=0.003), protein (p=0.001), fat intake (p=0.924), and physical fitness level.Conclusion: It was concluded that carbohydrates and proteins are associated with a physical condition. However, there is no relationship between fat intake and physical fitness level.